2007
DOI: 10.1016/j.cdp.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teamwork and system support on colorectal cancer screening in primary care practices

Abstract: BACKGROUND-While cancer screening is generally increasing in the U.S., colorectal cancer (CRC) screening remains low. Most CRC screening interventions focus either on patients or individual clinicians without examining the office context in which CRC screening is implemented. This study examines whether primary care practices that involve staff in general forms of health education have higher CRC screening rates than practices that do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…7,8,27 We found that the presence of an electronic reminder system was positively associated with prevention scores. We could not determine whether this association was because the system was being used to identify eligible patients for preventive manoeuvres or whether the implementation of information technology indicated practice innovation and an orientation to quality.…”
Section: Discussionmentioning
confidence: 66%
“…7,8,27 We found that the presence of an electronic reminder system was positively associated with prevention scores. We could not determine whether this association was because the system was being used to identify eligible patients for preventive manoeuvres or whether the implementation of information technology indicated practice innovation and an orientation to quality.…”
Section: Discussionmentioning
confidence: 66%
“…12,19 Intervention programs created to encourage physicians to recommend CRC screening to patients have been effective in increasing screening rates among patients. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] These findings have opened a window of opportunity to increase CRC screening rates by changing healthcare professionals' practice rather than depending solely on patients' own motivation to undergo screening. Various plans have been proposed to change primary care practice in ways that would make it easier and more consistent for physicians to recommend CRC screening to their patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Health Interview Survey, 53% of individuals 50 years and older reported having undergone screening either by FOBT or endoscopy in 2008 [8]. There are several potential reasons for this low screening rate, ranging from lack of patient knowledge, low level of public and professional enthusiasm, multiple screening modalities, lack of insurance coverage [9][10][11], cultural [12,13] and system level factors [14,15], as well as physician-related barriers [16,17]. A key barrier to enhanced screening rates is lack of provider recommendations given that physician recommendation to undergo screening has been shown to predict screening uptake [11,18,19].…”
Section: Introductionmentioning
confidence: 97%